2001
DOI: 10.1128/aac.45.6.1649-1653.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the 8-Methoxy Group of Gatifloxacin to Resistance Selectivity, Target Preference, and Antibacterial Activity against Streptococcus pneumoniae

Abstract: Gatifloxacin (8-methoxy, 7-piperazinyl-3-methyl) at the MIC selected mutant strains that possessed gyrA mutations at a low frequency (3.7 ؋ 10 ؊9 ) from wild-type strain Streptococcus pneumoniae IID553. AM-1147 (8-methoxy, 7-piperazinyl-3-H) at the MIC or higher concentrations selected no mutant strains. On the other hand, the respective 8-H counterparts of these two compounds, AM-1121 (8-H, 7-piperazinyl-3-methyl) and ciprofloxacin (8-H, 7-piperazinyl-3-H), at one and two times the MIC selected mutant strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…The alterations to the structure of the older-generation fluoroquinolones improve the spectrum of activity of fourth-generation fluoroquinolones to include strains of Staphylococcus and Streptococcus and species otherwise resistant to older-generation fluoroquinolones. 23,24 These new fourth-generation fluoroquinolones are particularly needed because the incidence of endophthalmitis is on the rise, 22,25 especially after clear corneal incision cataract surgery. 22,26 It has been demonstrated that perioperative treatment with a prior-generation fluoroquinolone is efficacious in eliminating bacteria found in the external ocular adnexa, the most likely source of the inoculum of bacteria during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations to the structure of the older-generation fluoroquinolones improve the spectrum of activity of fourth-generation fluoroquinolones to include strains of Staphylococcus and Streptococcus and species otherwise resistant to older-generation fluoroquinolones. 23,24 These new fourth-generation fluoroquinolones are particularly needed because the incidence of endophthalmitis is on the rise, 22,25 especially after clear corneal incision cataract surgery. 22,26 It has been demonstrated that perioperative treatment with a prior-generation fluoroquinolone is efficacious in eliminating bacteria found in the external ocular adnexa, the most likely source of the inoculum of bacteria during cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is whether the recent introduction into the clinic of gatifloxacin, a fluoroquinolone that has DNA gyrase (gyrA/B) as its primary target (5), and moxifloxacin, which may target DNA gyrase (6), will affect the prevalence and profile of single QRDR mutants. According to their mechanisms of action, gatifloxacin and moxifloxacin would be expected to select preferentially for gyr (A/B) mutations (5,6). It remains to be determined how the addition of DNA gyrase single mutants into a population that already contains topoisomerase IV single mutants will affect the emergence of fluoroquinolone-resistant strains within S. pneumoniae, a species known to efficiently exchange DNA by transformation.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that the C-8-OMe functionality of moxifloxacin confers a dual targeting of topoisomerase IV and DNA gyrase, thus helping to explain the effect of this functional group in restricting selection of resistant organisms (11,26,27). Levofloxacin, in contrast, appears to preferentially target topoisomerase IV in S. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%